Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues paper for Paraguay discusses how capital inflows contributed to credit expansions. Capital inflows contribute to a rapid expansion of private credit, exacerbating credit and business cycles. These effects are stronger under more rigid exchange rate arrangements and in economies that are more closed to trade. Macroeconomic evidence for Paraguay suggests that local firms might have experienced a relaxation of credit constraints during the high capital inflows phase. Evidence also shows that consumption, investment, and output has grown above trend alongside a strong credit growth.